Vitamin D Deficiency and Survival in Children after Hematopoietic Stem Cell Transplant - Wallace, Gregory (Biol Blood Marrow Transplant, 2015)
Vitamin D has endocrine function as a key regulator of calcium absorption and bone homeostasis and also has intracrine function as an immunomodulator. Vitamin D deficiency before hematopoietic stem cell transplantation (HSCT) has been variably associated with higher risks of graft-versus-host disease (GVHD) and mortality. Children are at particular risk of growth impairment and bony abnormalities in the face of prolonged deficiency. There are few longitudinal studies of vitamin D deficient children receiving HSCT, and the prevalence and consequences of vitamin D deficiency 100 days after transplant has been poorly studied. Serum samples from 134 consecutive HSCT patients prospectively enrolled into an HSCT sample repository were tested for 25-hydroxy (25 OH) vitamin D levels before starting HSCT (baseline) and at 100 days after transplantation. Ninety-four of 134 patients (70%) had a vitamin D level < 30 ng/mL before HSCT, despite supplemental therapy in 16% of subjects. Post-transplant samples were available in 129 patients who survived to day 100 post-transplant. Vitamin D deficiency persisted in 66 of 87 patients (76%) who were already deficient before HSCT. Moreover, 24 patients with normal vitamin D levels before HSCT were vitamin D deficient by day 100. Overall, 68% of patients were vitamin D deficient (<30 ng/mL) at day 100, and one third of these cases had severe vitamin D deficiency (<20 ng/mL). Low vitamin D levels before HSCT were not associated with subsequent acute or chronic GVHD, contrary to some prior reports. However, severe vitamin D deficiency (<20 ng/mL) at 100 days post-HSCT was associated with decreased overall survival after transplantation (P = .044, 1-year rate of overall survival: 70% versus 84.1%). We conclude that all pediatric transplant recipients should be screened for vitamin D deficiency before HSCT and at day 100 post-transplant and that aggressive supplementation is needed to maintain sufficient levels.